Prevalence of unmet needs for spasticity management in care home residents in the East Midlands, United Kingdom: a cross-sectional observational study. (November 2019) - Edwards, Laura; Ellis, Benjamin; Donnellan, Clare; Osman, Hanan; Haboubi, Naseer; Jones, Michael; Sunman, Wayne; Pinnington, Lorraine; Phillips, Margaret Frances
Objective: To establish the prevalence of unmet need for spasticity management in care home residents in two counties of the United Kingdom. Design: Cross-sectional observational study with a six-month follow-up arm for participants with identified unmet needs. Setting: 22 care homes in Derbyshire and Nottinghamshire. Subjects: 60 care home residents with upper motor neuron syndrome–related spasticity. Interventions: No intervention. When unmet needs around spasticity management were identified, the participant's general practitioner was advised of these in writing. Main measures: Resistance to Passive Movement Scale to assess spasticity; recording of (a) the presence of factors which may aggravate spasticity, (b) potential complications of spasticity, (c) spasticity-related needs and (d) current interventions to manage spasticity. Two assessors judged the presence or absence of needs for spasticity management and whether these needs were met by current care. Results: Out of 60 participants, 14 had no spasticity-related needs; 46 had spasticity-related needs; 11 had needs which were being met by current care and 35 participants had spasticity-related needs at baseline which were not being met by their current care. These were most frequently related to the risk of contracture development or problems with skin hygiene or integrity in the upper limb. In total, 6 participants had one or more pressure sores and 35 participants had one or more established joint contractures. A total of 31 participants were available for follow-up. Informing general practitioners of unmet needs resulted in no change to spasticity management in 23/31 cases. Conclusion: Care home residents in this study had high levels of unmet need for spasticity management.